2012
DOI: 10.1093/aob/mcs183
|View full text |Cite
|
Sign up to set email alerts
|

Micro-organisms behind the pollination scenes: microbial imprint on floral nectar sugar variation in a tropical plant community

Abstract: The results support the hypothesis that nectar yeasts impose a detectable imprint on community-wide variation in nectar sugar composition and concentration. Since nectar sugar features influence pollinator attraction and plant reproduction, future nectar studies should control for yeast presence and examine the extent to which microbial signatures on nectar characteristics ultimately have some influence on pollination services in plant communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 74 publications
5
77
0
Order By: Relevance
“…In H. foetidus, for example, reported variation between flowers, individuals, and populations in number of pollen tubes in the style (Herrera 2002) might be partly accounted for by the patchy distribution of M. reukaufii at different spatial scales. Nectar yeast abundance and variability levels comparable to or greater than those generated experimentally in this study seem to be the rule in natural habitats worldwide (Brysch-Herzberg 2004, Canto and Herrera 2012. This implies that the functional links between nectar yeasts, pollinator behavior, and plant reproductive success found here may also hold for other animal-pollinated plants elsewhere.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In H. foetidus, for example, reported variation between flowers, individuals, and populations in number of pollen tubes in the style (Herrera 2002) might be partly accounted for by the patchy distribution of M. reukaufii at different spatial scales. Nectar yeast abundance and variability levels comparable to or greater than those generated experimentally in this study seem to be the rule in natural habitats worldwide (Brysch-Herzberg 2004, Canto and Herrera 2012. This implies that the functional links between nectar yeasts, pollinator behavior, and plant reproductive success found here may also hold for other animal-pollinated plants elsewhere.…”
Section: Discussionsupporting
confidence: 73%
“…One infrequently acknowledged biotic factor potentially altering nectar features is nectardwelling yeasts, which recent studies have shown to abundantly populate animal-pollinated flowers worldwide (Brysch-Herzberg 2004, Herrera et al 2009). Among other effects, nectar yeasts can alter the composition and concentration of sugars and amino acids in nectar, contribute to the emission of floral volatiles, and warm the nectar in relation to the surrounding air (Raguso 2004, Wiens et al 2008, Canto and Herrera 2012. Microbial alterations of the intrafloral environment might influence the behavior of pollinators, which could in turn impinge on pollination success and fecundity of plants.…”
Section: Introductionmentioning
confidence: 99%
“…Nectar also can contain other sugars that are present in trace amounts, e.g., mannose, arabinose, xylose, maltose, melibiose and oligosaccharides such as raffinose, melezitose, stachyose and sorbitol (Nicolson and Thornburg 2007, and references therein). It is worth noting that nectar-dwelling microorganisms can significantly influence/modify nectar-sugar profiles (Canto and Herrera 2012;Vannette et al 2012;de Vega and Herrera 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts are very common in floral nectar. About half the samples collected in tropical and temperate plant communities proved positive for yeasts and showed a preponderance of basidiomycetous and ascomycetous species of the genera Cryptococcus, Metschnikowia, and Candida [61,62].…”
Section: Nectar Dwelling Microorganisms and Their Impact On Pollinatomentioning
confidence: 99%